Sustainability in the curriculum of the tourism professional at the Polytechnic State University of Carchi UPEC - Yacelga Rosero, Cecilia; Solórzano Robinson, Hada (Tierra Infinita, 2019)
In recent times, sustainability has become one of the paradigms for thinking about a future in which environmental, social and economic considerations are balanced in the pursuit of development and a better quality of life. Numerous studies confirm that tourism can adversely affect biodiversity and other natural resources and have adverse social and cultural impacts. Against this, it is stated that the damage generated by tourism must be addressed under a sustainable tourism approach in order to minimize the different impacts that may arise. The present study focuses on Higher Education and the great responsibility it has in the training of new professionals in the area of tourism. The objective is to analyze what is taught in relation to sustainability in the tourism career and identify skills and abilities that the professional has in the area to solve sustainable problems; for the achievement of the objective it is proposed to use the analytical method accompanied by the documentary review with the use of cards and matrices. The profiles and the micro-curriculum declaredby the engineering career in the engineering and the degree of the Polytechnic State University of Carchi UPEC are analyzed; a general diagnosis will be drawn up in relation to the incorporation of sustainability in them. It is established that the thematic incorporation is still in the initial phase and the new concepts and practices related to sustainability are absent in the study plans.
Keywords: Curriculum; Sustainability; Tourism; Higher Education